Evaluation of Consumption of Poultry Products Enriched with Omega-3 Fatty Acids in Anthropometric, Biochemical, and Cardiovascular Parameters - José Arias-Rico; Martha Izbeth Cerón-Sandoval; Eli Mireya Sandoval-Gallegos; Esther Ramírez-Moreno; Trinidad Lorena Fernández-Cortés; Judith Jaimez-Ordaz; Elizabeth Contreras-López; Javier Añorve-Morga (Journal of Food Quality, 2018)
An alternative for prevention and treatment for cardiovascular diseases (CVD) is increasing the intake of bioactive compounds as omega-3. However, several countries as México do not consume regularly foods with high content of omega-3, mainly fish products due to cultural, social, and economic factors. Therefore, the addition of omega-3 in other food sources could contribute to completing the requirements established of these fatty acids. To evaluate the effect of the consumption of poultry products supplemented with omega-3 in healthy population, a phase 1, double blind randomized, controlled parallel-group trial was carried out. After 14 weeks, the supplemented group had an increase in HDL, reducing the atherogenic index. The supplementation with omega-3 in poultry products could contribute to a cardioprotective effect. It is necessary to complete studies with a higher evaluation period to determine the improvement in anthropometric and cardiovascular parameters.